2016
DOI: 10.1088/2040-8978/18/6/063003
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on biosensing and photonics with advanced nano-optical methods

Abstract: This roadmap, through the contributions of ten groups worldwide, contains different techniques, methods and materials devoted to sensing in nanomedicine. Optics is used in different ways in the detection schemes. Raman, fluorescence and infrared spectroscopies, plasmonics, second harmonic generation and optical tweezers are all used in applications from single molecule detection (both in highly diluted and in highly concentrated solutions) to single cell manipulation. In general, each optical scheme, through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 98 publications
0
57
0
Order By: Relevance
“…Particularly, in contrast to their plasmonic counterparts, dielectric nanoresonators do not suffer from inherent material absorption losses 14,15 and they can support BIC modes generating extremely sharp resonances and strong light confinement. Importantly, dielectric metasurfaces that exhibit these supercavity modes in visible and near infrared (NIR) wavelengths can be extremely responsive to the local refractive index (RI) changes induced by individual biomolecules, due to their spatial overlap with the surface-confined electromagnetic fields 16 . This is in contrast to conventional Mie-type resonances in silicon subwavelength nanoparticles 15 , which store the field mainly inside the high-index material.…”
Section: Metasurfaces Based On Resonant Subwavelength Photonic Structmentioning
confidence: 99%
“…Particularly, in contrast to their plasmonic counterparts, dielectric nanoresonators do not suffer from inherent material absorption losses 14,15 and they can support BIC modes generating extremely sharp resonances and strong light confinement. Importantly, dielectric metasurfaces that exhibit these supercavity modes in visible and near infrared (NIR) wavelengths can be extremely responsive to the local refractive index (RI) changes induced by individual biomolecules, due to their spatial overlap with the surface-confined electromagnetic fields 16 . This is in contrast to conventional Mie-type resonances in silicon subwavelength nanoparticles 15 , which store the field mainly inside the high-index material.…”
Section: Metasurfaces Based On Resonant Subwavelength Photonic Structmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Among metallic nanoparticles, gold NPs have attracted significant interest owing to their high chemical and physical stability, biocompatibility, photo-stability and large optical cross sections. [17][18][19] The SPR of gold NPs found applications in manifold or areas 20 that included optical sensing, 21,22 biolog-3 ical imaging, [23][24][25] plasmonic photo-thermal therapy, 4 molecular diagnostics, 2,24,26 surface-enhanced Raman spectroscopy, 2 metal-enhanced luminescence and plasmonic rulers. 3 Enormous research has focused on the plasmonic properties of Au NPs and significant breakthroughs were made in the field.…”
Section: Introductionmentioning
confidence: 99%
“…4). 10 In the near future, we expect more ultrashort peptides to be applied as bioimaging nanoprobes for SHG or other non-linear optical microscopy. Koizumi et al 77 showed dipeptide derivatives have strong SHG signals and these materials can be used as electro-optical switch.…”
Section: Bioimaging Nanoprobesmentioning
confidence: 99%